SYSTEMATIC LITERATURE REVIEW PENGEMBANGAN E-LKPD BERBASIS GAMIFIKASI BERBENTUK ZEP QUIZ UNTUK MENINGKATKAN HASIL BELAJAR SISWA KELAS V PADA PEMBELAJARAN IPAS DI SEKOLAH DASAR - Isti'ana; Titi Andaryani, Eka; Avrilianda, Decky; Widiarti, Nuni (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze the potential for developing gamification-based digital learning materials (E-LKPD) in the form of a ZEP Quiz to improve elementary school students’ science learning outcomes through a systematic literature review as a pre-development study. The study employed a Systematic Literature Review (SLR) following the PRISMA guidelines. The search was conducted on Google Scholar, ERIC, and Semantic Scholar, covering publications from 2021 to 2026. Of the 478 identified articles, 23 met the inclusion criteria and were analyzed thematically. The findings indicate that interactive E-LKPDs have been effective in improving learning outcomes, with an average N-Gain in the moderate-to-high range. Gamification through elements such as points, leaderboards, and immediate feedback consistently enhances student motivation and engagement. The ZEP Quiz platform offers advantages, including a 2D avatar-based metaverse environment, AI integration for question generation, and real-time analytics, making it an ideal medium for gamified E-LKPD. The integration of these three components has strong potential to improve IPAS learning outcomes through meaningful, interactive, and enjoyable learning experiences.